Analisis Laporan Keuangan Sebagai Alat untuk Menilai Kinerja Perusahaan pada PT. Astra International Tbk (Periode 2021-2025) - Faiza Rahma; Dalizanolo Hulu (CV. Lenggogeni Data Publishing, 2026)
This research seeks to evaluate the financial performance of PT Astra International Tbk over the 2021-2025 period employing a descriptive quantitative method. The data utilized consist of annual financial reports acquired via documentation analysis. The evaluation applies financial ratios encompassing liquidity, solvency, and profitability, which are subsequently benchmarked against industry norms to gauge the firm’s financial condition. Findings reveal that the company’s revenue exhibited an ascending pattern from 2021 to 2024, albeit with a downturn in 2025. Regarding liquidity, the firm maintains a satisfactory standing, evidenced by a current ratio exceeding 100% nevertheless, the quick ratio indicates that liquidity has not attained full optimality. In terms of solvency, the capital structure is deemed sound, characterized by stable debt proportions and managed financial risks. Meanwhile, profitability ratios rose during the initial phase of the study period but diminished toward its conclusion, though they persist at a reasonably solid level. In summary, the financial performance of PT Astra International Tbk is regarded as stable, albeit enhancements are required in asset utilization efficiency and profit maximization. This research is anticipated to furnish a thorough depiction of the company’s financial status and function as a foundation for managerial and investment decisions.